Penerapan Akuntansi Pertanggungjawaban Dalam Menilai Kinerja Bidang Perdagangan Dalam Negeri Pada Kegiatan Penerbitan Surat Izin Usaha Perdagangan (SIUP) Minuman Beralkohol (Studi Kasus Dinas Perindustrian dan Perdagangan Sumatera Utara) - Rahmah Sudana Siregar; Juliana Nasution (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
ABSTRACTIn every activity carried out by an organization, be it a company or agency, there needs to be accountability in terms of reporting. This accountability aims to see whether the activities carried out have achieved the goals or targets achieved. So that the implementation of this responsibility can also be seen from how much budget is poured for an activity and how the budget is realized. The comparison between the budget and its realization needs to be known in order to assess performance. So in this case, the purpose of this study is to find out how the implementation of budget accountability in the Issuance of Registration Business Permits (SIUP) in the Corporate Registration Business Institutional Section in the Domestic Trade Sector. This study uses qualitative research methods with interview and observation techniques. By looking at the accountability reports of related activities. From the results of this study, the implementation of budget accountability in related activities has been carried out properly by using a benchmark, namely the budget and its realization to assess the performance achieved. The achievement of physical performance reached 100% and the achievement between the budget and its realization reached 86%.Keywords: Accountability Accounting, Realization, Performance